Zoning of the city of Aktobe on the degree of pollution (Journal of Geography and Environmental Management, 2019)
In the article discusses the environmental factors of the agglomeration of Aktobe. Considering thesustainable development of urban agglomerations, it should be noted that the environmental pollutionproblems arise as a result of this interaction between nature and man, when anthropogenic load onthe territory exceeds the environmental features of this area, due to its natural resource potential andsustainability of natural systems to anthropogenic influences.